Innovative Arabic Vocabulary Assessment Instruments to Enhance the Speaking Skills of Grade X Students at MA Science and Technology Al Marzuqiyyah Sumedang (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2025)
The ability to speak Arabic is highly dependent on the mastery of active vocabulary. However, at MA Sains Teknologi Al Marzuqiyyah Sumedang, vocabulary evaluation is still administrative and based on memorization, thus failing to reflect students' ability to use vocabulary communicatively. This research uses a descriptive qualitative approach with an initial development stage orientation. Data were obtained through learning observations, in-depth interviews with teachers and students, and analysis of curriculum documents and previous evaluation instruments. All data were analyzed using Miles & Huberman's thematic analysis through the stages of data reduction, data display, and conclusion drawing. The results indicate that there is no specific instrument available to assess students' ability to use vocabulary in speaking. As a solution, an innovative assessment instrument was developed, comprising a thematic vocabulary list, functional speaking tasks such as picture description, storytelling, and role-playing, as well as an analytical rubric assessing semantic, syntactic, and pragmatic aspects. Teachers responded positively and considered this instrument to be more communicative and systematic compared to traditional evaluations. This research affirms the importance of shifting from memorization-based evaluation to performance-based evaluation and provides an initial foundation for further research to quantitatively test the instrument's effectiveness and expand its application to other Arabic language skills.